2015
DOI: 10.1055/s-0035-1547340
|View full text |Cite
|
Sign up to set email alerts
|

Common Carotid Artery Occlusion: A Single-Center Experience in 40 Cases

Abstract: artery occlusion (CCAO) has been little discussed in the literature compared with occlusion of the internal carotid artery (ICA). However, CCAO seems to be a different disease because of its presentation, treatment, and incidence.CCAO is diagnosed in approximately 3% of the symptomatic patients undergoing carotid angiography 1 and in only 1 to 5% of the patients with symptomatic cerebrovascular disease. 2,3 The development of exuberant collateral circulation and patency of the carotid bifurcation seems to prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…In fact, indications of stenting have been narrowed down to enlarging pseudoaneurysms and dissection with near-complete stenosis [14,15]. A review of patients undergoing CCA revascularization in the non-traumatic population also concluded that the benefits of traditional treatments in asymptomatic patients are uncertain [16].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, indications of stenting have been narrowed down to enlarging pseudoaneurysms and dissection with near-complete stenosis [14,15]. A review of patients undergoing CCA revascularization in the non-traumatic population also concluded that the benefits of traditional treatments in asymptomatic patients are uncertain [16].…”
Section: Discussionmentioning
confidence: 99%
“…The collateral circulation consists mainly from the vertebrobasilar system with cross-filling of the middle cerebral artery through the circle of Willis or through an ECA-ophthalmic artery anastomosis. Patients who occlude their carotid artery may present asymptomatic, especially if they have gradually developed an excessive collateral network, although the majority of such patients is symptomatic according to recent pooled data [ 2 , 8 ]. In the acute setting, most of them experience neurological defects ranging from amaurosis fugax or transient ischemic attack to a major disabling stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular recanalization has been described in limited cases as well. This is justified as chronic atherosclerotic plaques are usually calcified and guidewire and emboli protection devices may not be possible to cross the lesion [ 2 , 8 ]. We believe that this therapeutic approach should be considered only in extremely high-risk patients and by endovascular surgeons/ interventional specialists who have large experience.…”
Section: Discussionmentioning
confidence: 99%
“…Common carotid artery occlusion (CCAO) is a rare condition and is diagnosed in about 3% of symptomatic patients with cerebrovascular disease [ 5 ]. The risk factors of CCAO include hypertension (HTN), a history of smoking, and diabetes mellitus (DM) [ 6 , 7 ]. The blood supply to the eye stems from the common carotid artery, thus, a CCAO can present with ocular ischemic syndrome (OIS) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%